PENERAPAN SURGICAL SAFETY CHECKLIST UNTUK MENEKAN INSIDEN KESELAMATAN PASIEN KAMAR OPERASI - Sulistyo, Bambang; Dongoran, Haddan; Rulia, Rulia (Jurnal Inspirasi Ilmu Manajemen, 2024)
Operating room is a hospital facility that carries risk of medical injury and complications that endanger lives. There’re still near misses incidents although the surgical safety checklist is completed. The completion of the surgical safety checklist questionable.In-depth interviews were conducted with informants. Results of interviews carried out data reduction, data display (data presentation) and conclusion drawing or verification. Data was analyzed then conclusions were drawn. Efforts for patient safety have been going well by the PMKP team. Still those who were not disciplined in their implementation for SSCL. There is already socialization on filling out the SSCL, training is still under discussion. There is a guarantee of supervision of filling in and implementing the SSCL in the operating room in coordination with the nurse and PMKP team and this is done every day and recapped every month. The implementation of SSCL was carried out well by all staff in the surgical room and supervised by the head of the room. Time out still hasn't been done in the operating room. There are obstacles in implementing SSCL, especially the doctor's signature, and non-existent training. Rewards are not balanced with punishment and the number of anesthesia nurse is inadequate to ensure patient safety. There is still prone to patient safety incidents seen from the negative findings about SSCL. The implementation of SSCL is effective in reducing patient safety incidents’s number in the operating room, during the sign in, time out and sign out phases. Hospitals need to build good work teams, organize training related to the SSCL, implement supporting technology, and reinforce safety culture and supervision regarding filling and implementing SSCL.